1989
DOI: 10.1017/s0033291700024326
|View full text |Cite
|
Sign up to set email alerts
|

Needs for care among the relatives of long-term users of day care: A report from the Camberwell High Contact Survey

Abstract: SynopsisWe report the results of a survey of the burdens and needs for items of care of 45 supporters of long-term users of psychiatric day care facilities in Camberwell. The supporters reported high levels of disturbed behaviour and low levels of self-care skills in the attenders. They were also subject to high levels of social and economic burden, not all of which could be attributed to the attenders' problems. The needs assessment identified a large number of unmet needs, although the supporters themselves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 19 publications
2
39
1
5
Order By: Relevance
“…Harvey and McGrath 61 found that 40% of fathers whose wives had suffered from postpartum psychosis experienced a classifiable psychiatric disorderhigher than the 30% prevalence rate in the partners of general psychiatry cases. 48 The men had seldom been abusive before the offence. 7 Misinterpretation of the infant's behaviour seemed to be the primary motive in many of the cases studied.…”
Section: Infant Homicidementioning
confidence: 99%
“…Harvey and McGrath 61 found that 40% of fathers whose wives had suffered from postpartum psychosis experienced a classifiable psychiatric disorderhigher than the 30% prevalence rate in the partners of general psychiatry cases. 48 The men had seldom been abusive before the offence. 7 Misinterpretation of the infant's behaviour seemed to be the primary motive in many of the cases studied.…”
Section: Infant Homicidementioning
confidence: 99%
“…16 These carers have been found to worry a lot about the display of difficult behaviours, negative symptoms, attempts of patients to harm themselves and concern if the caregiver had done anything that may have made the patient ill. 17 Some studies have shown that approximately one third of caring relatives have elevated levels of anxiety or depression connected with the caring role. 18,19 While caregiving appraisals may impact the burden of cargiving, these appraisals are often influenced by several factors, i.e. education, employment or global assessment of functioning of the caregiver.…”
Section: Introductionmentioning
confidence: 99%
“…Ceux et celles qui se sont intéressés à connaître ce que les familles attendaient du système de soins par rapport aux troubles de leur parent ont fait ressortir de façon cohérente qu'elles désiraient: 1) dès le début de l'apparition des troubles, de l'information en ce qui a trait aux symptômes, au traitement (principalement l'administration de la médi-cation et ses effets secondaires) et au pronostic; 2) des conseils pratiques sur la gestion des épisodes psychotiques et sur la vie quotidienne avec leur parent, lors de visites à domicile ou autrement; 3) une continuité dans le soin offert; et 4) le développement de ressources communautaires (Bernheim et Switalski, 1988;Gregory, 1989;Guberman et al, 1991;Hatfield, 1979aHatfield, , 1979bHatfield, , 1987aMacCarthy et al, 1989;StOnge et Lavoie, 1987;Tessler et al, 1991;Zirul et al, 1989). De plus, certains mentionnent l'importance pour les familles que l'équipe de soins adopte une attitude plus favorable à leur égard (Atkinson, 1986;Johnson, 1990a;Zirul et al, 1989 Tessler et al (1991) ont mis en relief que 33 % de ces personnes n'avaient jamais eu de contacts avec l'équipe soignante.…”
Section: Les Soins Professionnels Et Les Personnes-soutiensunclassified
“…Dans la même veine, MacCarthy et al (1989) ont fait ressortir que 33,3% des 45 personnes-soutiens qu'ils ont interrogées, cohabitant avec une personne atteinte de troubles mentaux qui bénéficiaient du soutien d'une ressource d'un hôpital, soit un centre de jour ou l'hôpital de jour, n'avaient eu aucun contact avec l'équipe durant les trois mois précédant l'entrevue. Étant donné que ces personnes bénéficiaient d'un soutien accru d'une ressource hospitalière, on aurait pu s'attendre que les personnes-soutiens aient plus de contacts avec l'équipe traitante.…”
Section: Les Soins Professionnels Et Les Personnes-soutiensunclassified